The Gambia : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation highlights that the Gambian economy has performed well in recent years, despite a difficult global environment. The external current account deficit has widened in recent years, owing to weak tourism receipts and remittances and high global commodity prices. Executive Directors have commended the authorities for making progress in poverty reduction and achieving strong growth and low inflation despite a difficult global environment. Directors have welcomed the improved fiscal performance and supported the government's plans for additional fiscal consolidation in the period ahead.